Sufism’s Status as the Balance of Islamic Law - Mosa Alblezi; Mohd Aderi Che Noh; Anwar, Saiful (NAJAHA, 2022)
The primary desideratum of this paper is to ascertain whether the Sufis are a part of the formative paradigm of the Islamic sciences, respecting the scholars and laws, or is it a schism which is heterogenic to the Islamic sciences. The method used is the library. Processing and analyzing data through compiling, categorizing data, and looking for content links from various data obtained from the writings, thoughts and opinions of figures or experts. The essential aspiration must be to construct an authentic evaluation of the traditions of the antecedent aficionados of the ideology without embellishing their educations. Moreover, this paper will present Sufism as a variant of Islam compared to the typology established in the hermeneutics of the masses in the Occident. The people need to be made aware of the essence of spiritual Islam and consider the religion to be mundane and intolerant. This obliviousness is, of course, to be expected as Muslims themselves have diverted from the path of esoteric knowledge, once ingrained in the Muslim heritage for over a millennium. While the names of Ghazali and Rumi are renowned, their creed and methodologies are only sometimes evaluated or championed. For this purpose, a meticulous approach is necessitated, through which the reader will ascertain a more thorough and objective comprehension of the faith.